3T diffusion-weighted MRI in the response assessment of colorectal liver metastases after chemotherapy: Correlation between ADC value and histological tumour regression grading. Issue 91 (June 2017) - Donati, Francescamaria; Boraschi, Piero; Pacciardi, Federica; Cervelli, Rosa; Castagna, Maura; Urbani, Lucio; Falaschi, Fabio; Caramella, Davide
Highlights: Assessing tumour response to chemotherapy is crucial in patients with colorectal liver metastases. ADC values of 3T DW-MRI and histological TRG of colorectal liver metastases after preoperative chemotherapy significantly correlated. ADCe, ADCP and ADCc values of colorectal liver metastases were significantly different in the TRG classes. The entire tumour evaluation obtained the highest diagnostic accuracy for each TRG class. DW-MRI using quantitative analysis of ADC value could be proposed as a cancer biomarker. Abstract: Purpose: The purpose of the study was to correlate the apparent diffusion coefficient (ADC) values of diffusion-weighted MR imaging (DW-MRI) by 3T device with the histological tumour regression grading (TRG) analysis of colorectal liver metastases after preoperative chemotherapy. Materials and methods: Our study included thirty-five patients with colorectal liver metastases who had undergone MRI by 3T device (GE DISCOVERY MR750; GE Healthcare) after preoperative chemotherapy. DW-MRI was performed using a single-shot spin-echo echo-planar sequence with multiple b -values (0, 150, 500, 1000, 1500 s/mm 2 ), thus obtaining an ADC map. For each liver lesion (more than 1 cm in diameter) the fitted ADC values were calculated by two radiologists in conference and three ROIs were drawn: around the entire tumour (ADCe ), at the tumour periphery (ADCp ) and at the tumour center (ADCc ). All ADC values were correlated with histopathological findings after surgery. Hepatic metastases were pathologically classified into five groups on the basis of TRG. Statistical analysis was performed on a per-lesion basis utilizing the one-way analysis of variance (ANOVA). This retrospective study was approved by our institutional review board; written informed consent was obtained from all patients. Results: A total of 106 colorectal liver metastases were included for image analysis. TRG1, TRG2, TRG3, TRG4 and TRG5 were observed in 4, 14, 36, 35 and 17 lesions, respectively. ADCe and ADCp values were significantly higher in lesions classified as TRG1 (2.40 ± 0.12 × 10 −9 m 2 /s and 2.28 ± 0.26 × 10 −9 m 2 /s, respectively) and as TRG2 (1.40 ± 0.31 × 10 −9 m 2 /s and 1.44 ± 0.35 × 10 −9 m 2 /s), compared to TRG3 (1.16 ± 0.13 × 10 −9 m 2 /s and 1.01 ± 0.18 × 10 −9 m 2 /s), TRG4 (1.10 ± 0.26 × 10 −9 m 2 /s and 0.97 ± 0.24 × 10 −9 m 2 /s), and TRG5 (0.93 ± 0.17 × 10 −9 m 2 /s and 0.82 ± 0.28 × 10 −9 m 2 /s). ADCe, ADCp and ADCc values were significantly different in TRG classes (p < 0.0001). Statistical correlations were found between the ADCe, ADCp, ADCc values and the TRG classes (Spearman correlation coefficient were −0.568, −0.542 and −0.554, respectively). Conclusion: Our study showed a significant correlation between ADC values of 3T DW-MRI and histological TRG of colorectal liver metastases after preoperative chemotherapy.